Forests as Nature-Based Solutions: Ecosystem Services, Multiple Benefits and Trade-Offs (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The concept of Nature-based Solutions (NbS) is becoming increasingly relevant in international and European policy frameworks. In March 2022, the fifth session of the United Nations Assembly for the Environment (UNEA-5) adopted a formal “Resolution on Nature-based Solutions NbS for Supporting Sustainable Development”, in which an agreed definition of NbS was given, recognizing their important role in the global response to climate change and its social, economic, and environmental effects. Forest ecosystems, including natural forests, managed forests, agroforestry systems, and urban and peri-urban forests, can be considered as multifunctional NbS, delivering key ecosystem services to people and supporting biodiversity. However, for the effective implementation and mainstreaming of forests as NbS, several research gaps still need to be addressed.This collection of papers presents relevant results from scientific researchers about the ecosystem services provided by forests in natural and urban contexts, encompassing not only providing services, but also regulation and maintenance services, such as carbon and air pollution sink, as well as recreational services. The impacts of environmental changes on forest multifunctionality and services provision are also investigated. Case studies for monetary valuation, willingness to pay for ecosystem services, and cost/benefit analyses are presented. The potential trade-offs and synergies between services, which might result from different stakeholders’ perspective and management strategies, are identified and critically discussed, adopting a science–policy interface approach.